Fabrication of ferroelectric glass ceramics from (K0.5Na0.5)NbO3-SiO2-Al2O3glass system - Ploypailin Yongsiri (2018)
In this research, the fabrication of glass ceramics containing ferroelectric KNN crystals has been carried out in aluminosilicate glass system by using conventional mixed oxide technique in alumina crucible. Alumina was chosen to increase mechanical robust and the stability of KNN glass ceramic in ratio 0, 5, 10 and 15 mol%. The received glass ceramics were all transparent. The glasses were subjected to heat treatment processes at the temperature between 600 and 700°C in order to form the glass ceramics with desired crystal phases. X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques were used for phase identification and microstructural studies, respectively. The bulk crystallization of KAlSiO2phase was observed in the glass ceramics with heat treatment temperatures from 600 - 675°C while KNN phase started to appear at higher temperature of 700°C. The glass ceramic containing 23.75 mol% SiO2possesses the optimum values of dielectric constant (er): ∼260 and low dielectric loss (tand): ∼0.02 at 10 kHz in room temperature. Copyright © Taylor & Francis Group, LLC.